The Responsibilities of General Practitioners in Hiring Internsip Doctors in Independent Practices - Redika Janasuta, Putu Bagus; Huda, Mokhamad Khoirul (Kertha Patrika; Vol 45 No 1 (2023), 2023)
The government expects all health workers to be able to provide optimal quality health services without being forced into carrying out their duties and responsibilities, both in government and private hospital service facilities, independent clinics, and independent practice. When the general practitioner is unable to attend on a predetermined schedule, the replacement of medical services is replaced by an internship doctor. This study aims to analyze the legal norms and responsibilities of general practitioners who provide delegation to substitute doctors who are still with internsip program status if medical negligence occurs at an independent clinic. The research method used normative juridical with a conceptual and legal approach. There is still a void in the legal norms in the legislation regarding the duties and roles of internship doctors in replacing medical services in independent clinics. The responsibility of a general practitioner who delegates duties to a substitute doctor who is still in the internship program status is mandatory. Thus, if medical negligence occurs at an independent clinic caused by medical services performed by an internsip doctor, the general practitioner will also be responsible administratively, civilly, or criminally.